EFEKTIVITAS PEMBELAJARAN KONTEKSTUAL MELALUI COOKING CLASS UNTUK PEMBENTUKAN KARAKTER ANAK USIA DINI - Jumaisah Jumaisah (PERISKOP : Jurnal Sains dan Ilmu Pendidikan, 2022)
Character education is one of the important things that must be instilled in early childhood. Through character education, an individual is able to play a role as he should in accordance with the nature of being human. Instilling character values can be done through activities to get used to being disciplined and independent in doing something. Through these two things, students are able to obey the rules and norms that as individuals are able to regulate themselves. The purpose of this study was to find out the process of character formation, namely discipline and independence through cooking class activities every year at TK Aisyiyah 25 Jakarta, and to describe cooking class activities carried out by students at home and at school. The population of this research is Group B students of TK Aisyiyah 25 Jakarta. This type of research is a quantitative descriptive research using direct survey methods and through the Google form. The results of the study obtained data that cooking class activities with parental assistance were able to influence student discipline attitudes, namely an increase of 92.32%, students also experienced an increase in independence of 84.20%. In addition, the responses from students' parents while accompanying children in cooking class activities were in the very pleasant category of 89.10%.